Corporate financial policy - Agarwal, O. P. (Himalaya Pub. House, 2009)
UNIT-l FINANCIAL POLICY UNIT-2 CORPORATE FINANCIAL GOALS UNIT-3 MERGERS AND ACQUISITIONS UNIT-4 CORPORATE VALUATION BIBLIOGRAPHY.